Tectonic evolution of the Southern Espinhaço Front in Serra do Cipó-MG - Joncew, Henrique Chaves (2024)
The tectonic evolution of the Southern Espinhaço Front was characterized in the region of Serra do Cipó-MG, using geologic mapping and field structural, strain, quartz crystallographic axes patterns by EBSD and fluid inclusion analyses, as well radiometric dating by K-Ar and in situ Rb-Sr of mica and U-Pb of detrital zircons. The region was divided in two main tectonic domains: the Foreland (west) and the Fold-and-Thrust Belt (east). The stratigraphy of the Foreland Domain is composed by the São João da Chapada Formation (Espinhaço Supergroup), and the Sete Lagoas and Serra de Santa Helena formations (Bambuí Group). The Fold-and-Thrust Domain is made up by upper formations of the Espinhaço Supergroup Galho do Miguel, Santa Rita and Córrego dos Borges. The limit between these domains is the Southern Espinhaço Front, marked by a main thrust fault or shear zone, with a NNW-SSE trend, and stratigraphic inversion of the Santa Rita and Sete Lagoas formations. A series of parallel thrust faults are present in both domains, accompanied by development of east-dipping flattening foliations and stretch lineations, and structures associated with the deformation, such as tight folds and asymmetric kinematic indicators, all indicating tectonic vergence from east to west. In the Foreland Domain, the São João da Chapada Formation is a local rigid basement to the Bambuí Group, sitting below a basal detachment separating it from the Sete Lagoas Formation. Strain analysis showed predominant oblate ellipsoids, with east low-dipping flattening planes (XY) and lineations (X) coherent with the regional context. At intracrystalline level, quartz [c] and axes suggest a combination of pressure dissolution and dislocation glide mechanisms. Pressure dissolution is the primary deformation mechanism for the fine-grained fractions of the rocks, while dislocation glide is the main mechanism for the larger grains. The rhombohedral system is the most active for dislocation glide, but the basal system is also significant in the foreland domain. Fluid inclusion analysis has shown that the circulation of metamorphic fluids was very limited in the area during deformation. The populations of fluid inclusions in each compartment are different, suggesting most likely an origin from intra-basinal brines. By crossing metamorphic paragenesis, fluid inclusion, illite crystallinity and EBSD data, we estimate that deformation occurred within 300-411 ºC and 1.7-6.0 kbar ranges in the foreland, while the fold-and-thrust belt experienced conditions of 385-450 ºC and 2.8-8.0 kbar. In situ Rb-Sr dating of muscovite indicate a metamorphic peak age of 548.8 ± 17.1 Ma, while K-Ar ages of fine fractions of the same mineral yielded results of 510.3 ± 5.3 to 432.6 ± 7.5 indicating successive cooling stages. We propose that the fold-and-thrust belt evolved as a Coulomb wedge driven by the tectonic forces generated by the lateral spread and the buoyancy of the orogenic building. In this context, the region experienced progressive deformation, which caused crustal thickening until the system reached a critical taper condition, when a new thrust would cause the advance of the orogenic front onto the foreland, and the process would repeat itself until the orogenic activity ceased and isostatic equilibrium was achieved.